Development of peer-to-peer (P2P) internet online hybrid test system. - Pan, Peng
A new Internet online hybrid test system, designated the ?peer-to-peer (P2P) Internet online hybrid test system?, is proposed. In the system, the simulated structure is divided into multiple substructures, and each substructure is analysed numerically or tested physically in parallel at geographically distributed locations. The equations of motion are not formulated for the entire structure but for each substructure separately. Substructures are treated as highly independent systems, and only standard I/O, i.e. displacements and forces at the boundaries, are used as interfaces. A ?Coordinator? equipped with an iterative algorithm based on quasi-Newton iterations is developed to achieve compatibility and equilibrium at boundaries. A test procedure, featuring two rounds of quasi-Newton iterations and using assumed elastic stiffness, is adopted to avoid iteration for the substructure being tested physically. A fast and stable solution using a socket mechanism is developed for data exchange over the Internet. Demonstration tests applied to a base-isolated structure was conducted, and the results are compared with an online hybrid test using the conventional test method. The results obtained from the P2P Internet hybrid test match very closely those obtained from the conventional tests. Investigations are also carried out on time consumption and control accuracy. The results show that the Internet data exchange solution using the socket mechanism is fast, and tests were completed successfully under the constructed Internet online hybrid test environment.
Keywords: Online hybrid test; Substructuring; Internet; Peer-to-peer system; Quasi-Newton iteration; Base-isolation.